In vitro and in silico evaluation of the design of nano-phyto-drug candidate for oral use against Staphylococcus aureus - Budama-Kilinc, Yasemin; Gok, Bahar; Aluc, Cigdem Cetin; Kecel-Gunduz, Serda (PEERJ INC, 2023)
Onopordum acanthium is a medicinal plant with many important properties, such as antibacterial, anticancer, and anti-hypotensive properties. Although various studies reported the biological activities of O. acanthium, there is no study on its nano-phyto-drug formulation. The aim of this study is to develop a candidate nano-drug based on phytotherapeutic constituents and evaluate its efficiency in vitro and in silico. In this context, poly (lactic-co-glycolic acid) (PLGA) nanoparticles (NPs) of O. acanthium extract (OAE) were synthesized and characterized. It was determined that the average particle size of OAE-PLGA-NPs was 214.9 & PLUSMN; 6.77 nm, and the zeta potential was -8.03 & PLUSMN; 0.85 mV, and PdI value was 0.064 & PLUSMN; 0.013. The encapsulation efficiency of OAE-PLGA-NPs was calculated as 91%, and the loading capacity as 75.83%. The in vitro drug release study showed that OAE was released from the PLGA NPs with 99.39% over the 6 days. Furthermore, the mutagenic and cytotoxic activity of free OAE and OAE-PLGA-NPs were evaluated by the Ames test and MTT test, respectively. Although 0.75 and 0.37 mg/mL free OAE concentrations caused both frameshift mutation and base pair substitution (p < 0.05), the administered OAE-PLGA NP concentrations were not mutagenic. It was determined with the MTT analysis that the doses of 0.75 and 1.5 mg/mL of free OAE had a cytotoxic effect on the L929 fibroblast cell line (p < 0.05), and OAE-PLGA-NPs had no cytotoxic effect. Moreover, the interaction between the OAE and S. aureus was also investigated using the molecular docking analysis method. The molecular docking and molecular dynamics (MD) results were implemented to elucidate the S. aureus MurE inhibition potential of OAE. It was shown that quercetin in the OAE content interacted significantly with the substantial residues in the catalytic pocket of the S. aureus MurE enzyme, and quercetin performed four hydrogen bond interactions corresponding to a low binding energy of -6.77 kcal/mol with catalytic pocket binding residues, which are crucial for the inhibition mechanism of S. aureus MurE. Finally, the bacterial inhibition values of free OAE and OAE-PLGA NPs were determined against S. aureus using a microdilution method. The antibacterial results showed that the inhibition value of the OAE-PLGA NPs was 69%. In conclusion, from the in vitro and in silico results of the nano-sized OAE-PLGA NP formulation produced in this study, it was evaluated that the formulation may be recommended as a safe and effective nano-phyto-drug candidate against S. aureus.
Keywords: O; acanthium extract; PLGA nanoparticle; Antibacterial activity; Mutagenicity; Cytotoxicity; Molecular docking; MD; PLGA NANOPARTICLES; ACCURATE DOCKING; DELIVERY-SYSTEM; EXTRACT; ACID; IDENTIFICATION; OPTIMIZATION; DOXORUBICIN; ANTIOXIDANT; MECHANISMS; Science & Technology - Other Topics